Practical Competency Development In Mortgage Loan Services At Bank Tabungan Negara: Pengembangan Kompetensi Praktis Pada Layanan Pinjaman KPR Di Bank Tabungan Negara - Dinda Nur Ameliya; Kumara Adji Kusuma (International Consortium of Education and Culture Research Studies, 2024)
General Background Intense job market competition requires prospective workers to possess practical industry skills rather than relying solely on theoretical knowledge. Specific Background Bank Tabungan Negara prioritizes housing credit distribution for individuals with limited purchasing power, requiring meticulous administrative support within its consumer divisions. Knowledge Gap Students frequently lack direct exposure to the complex operational workflows, customer interactions, and administrative realities required in modern banking environments. Aims This study explores the experiences, skill acquisition, and networking opportunities gained during an immersive field practice to build high-quality human resources. Results Qualitative observational analysis reveals that active participation in document verification, transaction data entry, and customer interviews significantly builds professional capabilities. Furthermore, confronting workplace challenges, such as staff limitations and initial communication barriers, directly fosters adaptability and operational resilience. Novelty This report details the granular, day-to-day administrative procedures and interpersonal requirements of subsidized housing credit processing strictly from a trainee perspective. Implications Structured field practice successfully bridges the gap between academic theories and industry demands, shaping highly qualified, disciplined, and responsible professionals ready for employment. Highlights: Direct observation of credit distribution processes builds professional readiness and workforce discipline. Analyzing financial documents and customer transactions ensures accurate subsidized housing administration. Overcoming workplace communication barriers significantly improves interpersonal skills and operational adaptability. Keywords: Internship Program, Credit Administration, Human Resources, Financial Verification, Workplace Experience